2022
DOI: 10.3390/diagnostics12061391
|View full text |Cite
|
Sign up to set email alerts
|

T2*-Mapping of Knee Cartilage in Response to Mechanical Loading in Alpine Skiing: A Feasibility Study

Abstract: Purpose: This study intends to establish a study protocol for the quantitative magnetic resonance imaging (qMRI) measurement of biochemical changes in knee cartilage induced by mechanical stress during alpine skiing with the implementation of new spring-loaded ski binding. Methods: The MRI-knee-scans (T2*-mapping) of four skiers using a conventional and a spring-loaded ski binding system, alternately, were acquired before and after 1 h/4 h of exposure to alpine skiing. Intrachondral T2* analysis on 60 defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…A previous mechanical loading study detected a relevant decrease in T2* values of knee cartilage after 4 hours of alpine skiing, and T2* values increased above baseline overnight. 5 Behzadi et al also found significantly decreased T2* values in all cartilage segments after 45 minutes of long-distance running. 32 Marathon running seems to have reversed effects on T2* values, with two studies by Zhang and Hesper et al demonstrating increased T2* values after marathon running.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…A previous mechanical loading study detected a relevant decrease in T2* values of knee cartilage after 4 hours of alpine skiing, and T2* values increased above baseline overnight. 5 Behzadi et al also found significantly decreased T2* values in all cartilage segments after 45 minutes of long-distance running. 32 Marathon running seems to have reversed effects on T2* values, with two studies by Zhang and Hesper et al demonstrating increased T2* values after marathon running.…”
Section: Discussionmentioning
confidence: 86%
“…35 The T2* decrease may be due to collagen fiber deformation and increase of anisotropy and water squeezed out from the cartilage matrix. 5,32 Increased T2* values after marathon running may result from elevated mobility of water, degradation of proteoglycan, and loss of anisotropy of collagen fibers. 5,33,35 In our study, no significant difference was found in thickness and T2* values of deep cartilage after exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent techniques have shown the feasibility of compositional MRI in assessing cartilage overuse. The feasibility of normalT2* mapping of the knee cartilage in assessing the response to mechanical loading in skiing was demonstrated 98 . More specific biomechanical measures, such as strain mapping, were evaluated in the knee cartilage, 99 as shown in Fig.…”
Section: Emerging Methods For Quantitative Mri For Cartilagementioning
confidence: 99%
“…The feasibility of T * 2 mapping of the knee cartilage in assessing the response to mechanical loading in skiing was demonstrated. 98 More specific biomechanical measures, such as strain mapping, were evaluated in the knee cartilage, 99 as shown in Fig. 11, and intervertebral discs.…”
Section: Mri-based Biomechanical Assessmentmentioning
confidence: 99%